2011
DOI: 10.4314/thrb.v13i3.66915
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Anopheles gambiae s.l. and insecticide resistance profile relative to physicochemical properties of breeding habitats within Accra Metropolis, Ghana

Abstract: Malaria is endemic in Ghana as in most countries of sub-Saharan Africa. This study was conducted to characterize Anopheles gambiae s.l. and determine pyrethroid resistance profiles relative to physicochemical properties of breeding habitats in Accra, Ghana. Eight aquatic habitats containing Anopheles larvae were identified and from each habitat, larvae and water were sampled. Adult An. gambiae reared from larvae were morphologically identified and tested for permethrin (0.75%) and deltamethrin (0.05%) resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 38 publications
5
31
0
Order By: Relevance
“…This observation confirms work done by Yadouleton et al in Benin and Kabula et al in Ghana [4] [32] showing high insecticide resistance of A. gambiae s.l. within urban vegetable growing areas.…”
Section: Discussionsupporting
confidence: 92%
“…This observation confirms work done by Yadouleton et al in Benin and Kabula et al in Ghana [4] [32] showing high insecticide resistance of A. gambiae s.l. within urban vegetable growing areas.…”
Section: Discussionsupporting
confidence: 92%
“…In the study area, P. falciparum is the major malaria species and Anopheles gambiae sensu stricto the main vector [7–9]. AL has been used as the first-line treatment for uncomplicated malaria since 2006.…”
Section: Methodsmentioning
confidence: 99%
“…gambiae showed significant positive correlation of fluoride (r = 0.739, p = 0.036) with higher proportions of An. gambiae s.s. M-form in larval habitats [18]. In the present study, although fluoride showed significant weak positive correlation with immature density in general, fluoride along with TDS, EC, total hardness, chloride, and sulfate, indicated a very strong positive correlation in habitats where An.…”
Section: Discussionmentioning
confidence: 45%
“…stephensi preferred less nitrite content compared to Culex sp. and in Ghana where Anopheles gambiae preferred much less nitrite content (<0.005 mg/L) [18]. Furthermore, phosphate showed significant difference in habitats with Anopheles breeding and when co-inhabitation of Anopheles was observed with other mosquito species.…”
Section: Discussionmentioning
confidence: 99%